An antibody-based proximity labeling map reveals mechanisms of SARS-CoV-2 inhibition of antiviral immunity. Issue 1 (20th January 2022) - Zhang, Yuehui; Shang, Limin; Zhang, Jing; Liu, Yuchen; Jin, Chaozhi; Zhao, Yanan; Lei, Xiaobo; Wang, Wenjing; Xiao, Xia; Zhang, Xiuyuan; Liu, Yujiao; Liu, Linlin; et al.
Summary: The global epidemic caused by the coronavirus severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has resulted in the infection of over 200 million people. To extend the knowledge of interactions between SARS-CoV-2 and humans, we systematically investigate the interactome of 29 viral proteins in human cells by using an antibody-based TurboID assay. In total, 1, 388 high-confidence human proximal proteins with biotinylated sites are identified. Notably, we find that SARS-CoV-2 manipulates the antiviral and immune responses. We validate that the membrane protein ITGB1 associates angiotensin-converting enzyme 2 (ACE2) to mediate SARS-CoV-2 entry. Moreover, we reveal that SARS-CoV-2 proteins inhibit activation of the interferon pathway through the mitochondrial protein mitochondrial antiviral-signaling protein (MAVS) and the methyltransferase SET domain containing 2, histone lysine methyltransferase (SETD2). We propose 111 potential drugs for the clinical treatment of coronavirus disease 2019 (COVID-19) and identify three compounds that significantly inhibit the replication of SARS-CoV-2. The proximity labeling map of SARS-CoV-2 and humans provides a resource for elucidating the mechanisms of viral infection and developing drugs for COVID-19 treatment. Graphical abstract: Highlights: We provide 1, 388 high-confidence human proximal proteins of SARS-CoV-2 proteins ITGB1 associates with hACE2 to mediate SARS-CoV-2 entry NSP9 targets the methyltransferase SETD2 to block IFN-STAT1 signaling NSP14 and NSP16 block the IFN signaling through the Hippo pathway Abstract : Zhang et al. use a proximity labeling technology to identify human proximal proteins of SARS-CoV-2. They show that SARS-CoV-2 manipulates key cellular processes in antiviral and immune responses. They provide a resource for elucidating the mechanisms of SARS-CoV-2 infection and developing drugs for COVID-19 treatment.